Long-term oncological results after transanal total mesorectal excision for rectal carcinoma - Jeroen Hol; Stefan van Oostendorp; Jurriaan B. Tuynman; Colin Sietses (2019)
Abstract Background Transanal total mesorectal excision (TaTME) for mid and low rectal cancer has been shown to improve short-term outcomes, mostly due to lower conversion rates and with improved quality of the specimen. However, robust long-term oncological data supporting the encouraging clinical and pathological outcomes are lacking. Methods All consecutive patients undergoing TaTME with curative intent for mid or low rectal cancer in two referral centers in The Netherlands between January 2012 and April 2016 with a complete and minimum follow-up of 36 months were included. The primary outcome was local recurrence rate. Secondary outcomes were disease-free survival, overall survival and development of metastasis. Results There were 159 consecutive patients. Their mean age was 66.9 (10.2) years and 66.7% of all patients were men. Pathological analysis showed a complete mesorectum in 139 patients (87.4%), nearly complete in 16 (10.1%) and an incomplete mesorectum in 4 (2.5%). There was involvement of the CRM (< 1 mm) in one patient (0.6%) and no patients had involvement of the distal margin (< 5 mm). Final postoperative staging after neoadjuvant therapy was stage 0 in 11 patients (6.9%), stage I in 73 (45.9%), stage II in 31 (19.5%), stage III in 37 (23.3%) and stage IV in 7 (4.4%). The 3-year local recurrence rate was 2.0% and the 5-year local recurrence rate was 4.0%. Median time to local recurrence was 19.2 months. Distant metastases were found in 22 (13.8%) patients and were diagnosed after a median of 6.9 months (range 1.1–50.4) months. Disease-free survival was 92% at 3 years and 81% at 5 years. Overall survival was 83.6% at 3 years and 77.3% at 5 years. Conclusions The long-term follow-up of the current cohort confirms the oncological safety and feasibility of TaTME in two high volume referral centers for rectal carcinoma. However, further robust and audited data must confirm current findings before widespread implementation of TaTME.